Akuntansi Aset Kripto dan Tokenisasi Aset sesuai Standar IFRS: Keseragaman dan Ketidakkonsistenan Pelaporan - Andrian Anwar L Nata; Novi Riani (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2026)
This study examines accounting practices for crypto assets and real-world asset tokenization following the latest IFRS standards, including IFRS 16 issued in 2024. It analyzes 25 Indonesian entities’ financial statements from 2024–2025 using descriptive qualitative and comparative content analysis. The results show that while 60% of entities now classify major crypto assets under IFRS 16, 40% still apply divergent treatments. Inconsistency is most severe for asset tokenization, with no uniform recognition or measurement rules, leading to value differences of 28-47% for identical underlying assets. Key causes include unclear standard guidance, unique multi-function token characteristics, and delayed local convergence. These findings undermine comparability and reliability of financial information. The study proposes targeted standard improvements to achieve consistent reporting.